2019
DOI: 10.1103/physreve.100.012609
|View full text |Cite
|
Sign up to set email alerts
|

Milling and meandering: Flocking dynamics of stochastically interacting agents with a field of view

Abstract: We introduce a stochastic agent-based model for the flocking dynamics of self-propelled particles that exhibit velocity-alignment interactions with neighbours within their field of view. The stochasticity in the dynamics of the model arises purely from the uncertainties at the level of interactions. Despite the absence of attractive forces, this model gives rise to a wide array of emergent patterns that exhibit long-time spatial cohesion. In order to gain further insights into the dynamical nature of the resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…These group-level properties influence the level of alignment in simulation and empirical studies and describe the spatial structure and dynamics in animal groups ( Vicsek et al 1995 ; Ballerini et al 2008 ; Strömbom 2011 ). Spatial shoal spread and sub-group size influence collective motion, as less spread-out groups and larger groups are generally more aligned, while meandering describes group dynamics and is not expected to either increase or decrease with the level of alignment ( Vicsek et al 1995 ; Vicsek and Zafeiris 2012 ; Bagarti and Menon 2019 ). Meandering was calculated as the median across all fish per shoal for every frame.…”
Section: Methodsmentioning
confidence: 99%
“…These group-level properties influence the level of alignment in simulation and empirical studies and describe the spatial structure and dynamics in animal groups ( Vicsek et al 1995 ; Ballerini et al 2008 ; Strömbom 2011 ). Spatial shoal spread and sub-group size influence collective motion, as less spread-out groups and larger groups are generally more aligned, while meandering describes group dynamics and is not expected to either increase or decrease with the level of alignment ( Vicsek et al 1995 ; Vicsek and Zafeiris 2012 ; Bagarti and Menon 2019 ). Meandering was calculated as the median across all fish per shoal for every frame.…”
Section: Methodsmentioning
confidence: 99%
“…Each agent thus processes information within its field of view, related to the position and/or direction of movement of neighbours, to make a decision on its own direction of movement. To capture features of the emergent behaviour observed in natural bird flocks, various models have also incorporated different aspects of the processing of visual information, including variability in the field of view [22,23], an explicit attraction to facilitate flock cohesion [24], and the role of social hierarchy within the flocks [25].…”
Section: Collective Motion In Living Systemsmentioning
confidence: 99%
“…[2][3][4][5] Emergence of rotating structures from the collective motion of active agents is a fascinating phenomenon observed in nature, from swimming bacteria on the micro-meter scale [6][7][8][9] to flocks of plant-animal worms, 10 processionary caterpillars, 11 ants, 12 tadpoles, 13 plankton and fish on the meter scale. [14][15][16] Such an emergent collective motion can be classified into swarm, polarized and milling (vortex) states 17 with the milling one typically associated with confined geometry, 18,19 orientational asymmetry by introducing a blind angle [20][21][22] or external field. [23][24][25][26][27][28] In the presence of an alternating electric field, experiments found that spherical particles with dipole moments can be self-propelled and can form a transient/ stable rotating cluster.…”
Section: Introductionmentioning
confidence: 99%